Sistema de gestión académica vía web para el Colegio Fiscomisional La Dolorosa. - Viñan Ludeña, Marlon Santiago (2010)
This research work involves as main goal the development of a web academic management system for the High School "La Dolorosa," which enables to optimize some of the academic process that takes place in the institution, processes such as registration students, entering student grades and attendance records, process that teachers and inspectors, respectively may be made from any place and generate reports showing the results of students academic performance. In addition to optimize the time in the development process, the system improves the institutional image of educational entity, as it is important that the institution is kept updated about the importance of taking technological development with the educational field.